HUKUM PIDANA MERUPAKAN HUKUM JELEK - Laia, Aturkian (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
Criminal law is a bad law, if a criminal sentence is imposed on someone, it will experience such a heavy misery, criminal law is no longer relevant to its implementation and what is most feared in criminal law is its implementation by law enforcers who have the authority which is still being influenced. by political interests. The paradigm of criminal law adopted is the paradigm of modern criminal law, which is not retributive. In this study, there are several problem formulations, namely first, what makes criminal law a bad law? second, what is the paradigma of modern criminal law? and in this study has a normative research method.